2020
DOI: 10.1111/are.15052
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of antibiotic‐resistant bacteria in freshwater fish farms

Abstract: The emergence of antibiotic‐resistant bacteria (ARBs) has become a threat to the aquatic industry. Virulent bacterial spp. namely Aeromonas hydrophila, A. veronii, Pseudomonas fluorescens and P. aeruginosa that were isolated from Nile tilapia (Oreochromis niloticus) and grey mullet (Mugil cephalus) were collected from freshwater fish farms at three different sites, and their associated antibiotic‐resistant genes (ARBs) were further characterized. The ARGs for sulphonamide and tetracycline were the most prevale… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 89 publications
0
16
0
Order By: Relevance
“…The secondary metabolites from the cultures of endophytic fungi have been originate to have cytotoxic, antiviral, antimicrobial and anticancer activities (Nisa et al, 2015). The outcomes of the present study shown that out of 217 fish samples examined, 13.3% ( 23 The extensive use of antimicrobials in husbandry and aquaculture promotes the emergence of antimicrobial-resistant zoonotic pathogens (Sherif et al, 2021). Twenty two antibiotics belonged to 14 different antibiotic groups were tested against 30 isolates of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…The secondary metabolites from the cultures of endophytic fungi have been originate to have cytotoxic, antiviral, antimicrobial and anticancer activities (Nisa et al, 2015). The outcomes of the present study shown that out of 217 fish samples examined, 13.3% ( 23 The extensive use of antimicrobials in husbandry and aquaculture promotes the emergence of antimicrobial-resistant zoonotic pathogens (Sherif et al, 2021). Twenty two antibiotics belonged to 14 different antibiotic groups were tested against 30 isolates of P. aeruginosa.…”
Section: Discussionmentioning
confidence: 81%
“…who are responsible for choosing effective antibiotics that can be used for the treatment and prevention of disease (El-Bahar et al, 2019 andSherif et al, 2021 ). Commercial use of antibiotics in aquaculture needs to be reduced and replaced by other equally effective and non-resistance causing natural and bioactive products.…”
mentioning
confidence: 99%
“…Antimicrobial resistance genes for tetracycline and sulphonamide were predominantly isolated from highly virulent bacterial species such as A. hydrophila, A. veronii, P. aeruginosa and P. fluorescens from O. niloticus and M. cephalus cultured in freshwater fish farms in Egypt (Sherif et al, 2020). Similarly, tetracycline-resistant Photobacterium sp., Vibrio sp., Pseudomonas sp., Alteromonas sp., Citrobacter sp.…”
Section: Ta B L E 1 (Continued)mentioning
confidence: 99%
“…niloticus and M . cephalus cultured in freshwater fish farms in Egypt (Sherif et al, 2020). Similarly, tetracycline‐resistant Photobacterium sp., Vibrio sp., Pseudomonas sp., Alteromonas sp., Citrobacter sp.…”
Section: Incidence Of Antimicrobial Resistance In Freshwater Aquaculturementioning
confidence: 99%
“…Aeromonas hydrophila is one of the most common pathogenic bacteria causing disease among cultured and wild fish and restricting the development of commercial aquaculture throughout the world (Moustafa et al, 2020). Besides Oreochromis niloticus (Ibrahem et al, 2008), susceptibility to and pathogenicity of A. hydrophila have been reported in a variety of freshwater species like Clarias batrachus (Sherif et al, 2021), Cyprinus carpio (Citarasu et al, 2011) and Channa striata (Duc et al, 2013). A. hydrophila infection has often been associated with skin lesions, ulcers, tail and fin rot, haemorrhagic septicaemia over the body, necrosis in the liver and kidney of fish (Hassan et al, 2020).…”
Section: Introductionmentioning
confidence: 99%